A computational framework for impact fracture analysis of laminated glass: An extrinsic cohesive shell approach. (June 2020) - Wang, Di; Chen, Shunhua; Xu, Wei; Zang, Mengyan; Yoshimura, Shinobu
Highlights: A computational framework based on a cohesive shell model is proposed. An edge-edge contact approach is developed for glass cracks. A tied contact method is developed for the laminated glass model. A single surface contact algorithm is developed for glass and impactor. Impact fracture simulation results agree well with the experiment ones. Abstract: The purpose of this work is to propose a computational framework for impact fracture of laminated glass. The novel computational framework is based on a newly proposed extrinsic cohesive shell model that is theoretically more accurate than the element deletion method and the intrinsic cohesive model to describe fracture in thin-shell glass layers. A laminated glass model is established, where the glass is discretized into shell elements and the PVB film is modelled by solid elements. The bonding between glass and PVB is described via a developed tied contact method. A single surface contact algorithm is developed for the interaction between impactor and glass. Cohesive shell elements are adaptively inserted into the common boundaries between shell elements along with the growth of glass cracks. An edge-edge contact approach is developed to properly describe the interaction between glass cracks. Several simple examples are performed to validate the effectiveness of the proposed contact algorithms. Finally, the developed numerical framework is applied to the impact fracture simulation of a laminated glass plate. The simulation results are found to be in good agreement with the experimental ones, which validates the capacity of the computational framework in impact fracture analysis of laminated glass.